Unconjugated bilirubin activates and damages microglia - Gordo, Ana C. (2015)
Microglia are the resident immune cells of the brain and are the principal source of cytokines produced during central nervous system inflammation. We have previously shown that increased levels of unconjugated bilirubin (UCB), which can be detrimental to